Tetrabenzononacene: “Butterfly Wings” stabilize the core - Müller, Matthias; Maier, Steffen; Tverskoy, Olena; Rominger, Frank; Freudenberg, Jan; Bunz, Uwe H. F. (Angewandte Chemie. International edition, 2020)
Attachment of four benzo units electronically stabilizes a nonacene core without heteroatom substitution at/on the aromatic backbone. The four benzo units blueshift the absorption spectrum in compari...